2013
DOI: 10.1080/02614367.2013.833973
|View full text |Cite
|
Sign up to set email alerts
|

Elite sport culture and policy interrelationships: the case of Sprint Canoe in Australia

Abstract: In recent years, elite sport policy has received considerable research attention. However, to date the emphasis of such studies has been the examination of policies as stand-alone entities and the ways each policy may impact athlete performance rather than how policies influence each other. This study explores elite sport policy interrelationships in order to explain the dynamic links between policies and how they may affect performance. To explore these links in depth interviews with coaches, high performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 25 publications
(30 reference statements)
2
24
0
4
Order By: Relevance
“…The management of high-performance sport (HPS) is an all-encompassing umbrella term that is inclusive of macro-, meso-and micro-level factors that contribute to elite sport success, including the services provided by these performance-related experts (Smolianov, Gallo, & Naylor, 2014). Within this complex, multi-disciplinary team, athletes continue to maintain that access to excellent coaching is the most important support service they could receive (Sotiriadou, Gowthorp, & De Bosscher, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The management of high-performance sport (HPS) is an all-encompassing umbrella term that is inclusive of macro-, meso-and micro-level factors that contribute to elite sport success, including the services provided by these performance-related experts (Smolianov, Gallo, & Naylor, 2014). Within this complex, multi-disciplinary team, athletes continue to maintain that access to excellent coaching is the most important support service they could receive (Sotiriadou, Gowthorp, & De Bosscher, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, as de Haan and Knoppers argue (2019), coaches are themselves products of the sport system and are unlikely to be advocates of equality, or agents of social change, if they are not part of a gender-inclusive organisational culture. In their study on elite sport culture and policy interrelationships, Sotiriadou et al (2014) drew comparisons between organisational culture and sport-specific culture. In both these contexts, culture is likely to be an environmental factor that could influence coaches' experience.…”
Section: Introductionmentioning
confidence: 99%
“…Böhlke & Robinson, 2009;Brouwers, Sotiriadou, & De Bosscher, 2014;Robinson & Minikin, 2012;Sotiriadou, Gowthorp, & De Bosscher, 2014;Truyens, De Bosscher, Heyndels, & Westerbeek, 2013), because "success of countries tends to be concentrated in sports or specific events, in other words, countries typically specialize" (Truyens et al, 2013, p.1). What can be concluded from these studies is that there exists considerable overlap in what has been identified as common ingredients of successful elite athlete development, whether it is at a sport-specific or overall national level.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…see list above), culture (e.g. Sotiriadou, Gowthorp, & De Bosscher, 2014), sport development (Smolianov, Murphy, McMahon, & Naylor, 2015), gender (e.g. De Haan, Sotiriadou, & Henry, 2016;Greenhill, Auld, Cuskelly, & Hooper, 2009) and agency theory (Gowthorp, Toohey, & Skinner, 2017).…”
Section: Defining Hp Sport and Its Unique Characteristicsmentioning
confidence: 99%